Indonesian Coal Exports: Dynamic Panel Analysis Approach - Ambya, Ambya; Hamzah, Lies Maria (International Journal of Energy Economics and Policy, 2022)
Coal is a mineral fuel commodity considered important as a source ofenergy and is traded among countries. Indonesia is one of the largest coal producing countries in the world. This study aimed to analyse the relationship between the net export volume, GDP per capita of destination countries, real exchange rate, and Indonesian coal export prices. The existence of a causal relationship between exports and economic growth shows that there is a relationship between net exports and future economic growth. Economic growth is an increase in people's per capita income without paying attention to changes in the economic structure.The study uses panel data of 5 biggest coal trading partner countries of Indonesia during the period 2015-2019, by using the dynamic panel analysis method, where a dependent variable is not only determined by the value of independent variables at the research period, but is also determined by the value of previous period. The dynamic panel method is characterized by the lag of the dependent variable which is correlated with the residual among the independent variables. The dynamic panel data regression method can be used to determine the short-term effect,and the long-term effect as well.Based on the estimation results of the Generalized Method of Moment (GMM) Arellano Bond, in the study period the exchange rate and export prices had a significant negative effect on the volume of Indonesian coal exports. GDP per capita has no significant effect on the volume of Indonesia's coal exports.Furthermore, the short-term elasticity approach for the exchange rate is -0.029159 and for the long term is 0.3616521. These results indicate that the calculation of the short-term and long-term elasticity of the exchange rate (ER) is inelastic and negative with different magnitudes. In addition, it explains that in the short term an increase in the exchange rate of 1 percent will reduce net exports in the short term by 2.9 percent.